A coupled Volume of Fluid and Immersed Boundary Method for simulating 3D multiphase flows with contact line dynamics in complex geometries. (20th July 2017) - Patel, H.V.; Das, S.; Kuipers, J.A.M.; Padding, J.T.; Peters, E.A.J.F.
Highlights: We present a 3D coupled VOF and sharp interface-implicit IBM for multiphase flows. Contact line dynamic is resolved by applying a contact angle boundary conditions. Extensive validation cases are presented for static and dynamic contact angles. The simulated contact line dynamics with and without using IBM are compared. Pore-scale water flooding process through BCC and FCC structures are presented. Abstract: A numerical methodology is presented for simulating 3D multiphase flows through complex geometries on a non-body conformal Cartesian computational grid. A direct forcing implicit immersed boundary method (IBM) is used to sharply resolve complex geometries, employing the finite volume method (FVM) on a staggered grid. The fluid-fluid interface is tracked by a mass conservative sharp interface volume of fluid (VOF) method. Contact line dynamics at macroscopic length scale is simulated by imposing the apparent contact angle (static or dynamic) as a boundary condition at the three-phase contact line. The developed numerical methodology is validated for several test cases including the equilibrium shape of a droplet on flat and spherical surfaces, the temporal evolution of a droplet spreading on a flat surface. The obtained results show an excellent correspondence with those derived analytically or taken from literature. Furthermore, the present model is used to estimate, on a pore-scale, the residual oil remaining in idealized porous structures after water flooding, similar to the process used in enhanced oil recovery (EOR).